Targeting the chemokine receptor CXCR4 with histamine analog to reduce inflammation in juvenile arthritis - Bekaddour, Nassima; Smith, Nikaïa; Beitz, Benoit; Llibre, Alba; Dott, Tom; Baudry, Anne; Korganow, Anne-Sophie; Nisole, Sébastien; Mouy, Richard; Breton, Sylvain; Bader-Meunier, Brigitte; Duffy, Darragh; et al. (Frontiers in Immunology, 2023)
Among immune cells, activated monocytes play a detrimental role in chronic and viral-induced inflammatory pathologies. The uncontrolled activation of monocytes and the subsequent excessive production of inflammatory factors damage bone-cartilage joints in Juvenile Idiopathic Arthritis (JIA), a childhood rheumatoid arthritis (RA) disease. The moderate beneficial effect of current therapies and clinical trials highlights the need of alternative strategies targeting monocytes to treat RA disease. Here, we show that targeting CXCR4 with small amino compound such as the histamine analog clobenpropit (CB) inhibits spontaneous and induced-production of a set of key inflammatory cytokines by monocytes isolated from blood and synovial fluids of JIA patients. Moreover, daily intraperitoneal CB treatment of arthritic mice results in significant decrease in circulating inflammatory cytokine levels, immune cell infiltrates, joints erosion, and bone resorption leading to reduction of disease progression. These overall data show that targeting CXCR4 with CB-like molecules may represent a promising therapeutic option for chronic and viral-induced inflammatory diseases.